(untitled) (Italian Journal of Public Health, 2010)
Background: The primary causes of undernutrition in India are its large population, socio-economic differences and inadequate access to health facilities. Nutritional assessments among adolescents are important as they are the future parents and constitute a potentially susceptible group. Studies on the assessment of nutritional status of adolescents are less in number and a National database has not yet been developed. The present cross-sectional investigation evaluates the prevalence of undernutrition among rural adolescents (10 years - 17 years) from Darjeeling District, West Bengal, India. Methods: The present investigation was conducted among 726 rural school-going adolescents (376 boys and 350 girls) belonging to the Rajbanshi, Bengali Muslim and Bengali Caste communities. The nutritional status was assessed in terms of stunting (Height-for-age below 3rd percentile) and thinness (BMI-for-age below 5th percentile). Results: The overall prevalence of stunting and thinness were found to be 46.6% and 42.4% respectively. A high prevalence of stunting was found among boys (43.1%) and girls (50.3%) (p>0.05). The highest prevalence of stunting was observed among boys of 17 years (63.6%) and among girls of 15 years (70.0%). The overall mean BMI for girls was slightly higher than boys (16.8 ± 3.4 kg/m2 and 15.9 ± 2.1 kg/m2 respectively). A higher prevalence of overall thinness was found among boys (53.1%) than girls (32.0%) (p<0.05). Conclusions: There was a very high prevalence stunting and thinness among the boys and girls. There was a significant difference in the prevalence of undernutrition in terms of age and sex amongst them. Nutritional intervention is necessary to ameliorate their nutritional status. The results of the present investigation will help policy makers to formulate various developmental and health care programmes.